Accounting, non-governmental organizations and civil society: The importance of nonprofit organizations to understanding accounting, organizations and society - Hall, Matthew; O'Dwyer, Brendan (Accounting, Organizations and Society, 2017)
This introductory essay illustrates how our understanding of accounting, organizations and society can be enriched by closely studying the character and contexts evident in non-governmental organizations (NGOs) and non-profit organizations. These organizations represent diverse, complex, and frequently atypical contexts. We contend that these contexts are especially enthralling for accounting scholars given their performance measurement challenges, accountability to diverse sets of stakeholders, and the need to frequently balance and reconcile logics of efficiency and effectiveness. To support our contentions, we unpack a number of distinct control and accountability-related themes underlying the four papers included in this Special Issue. We reflect on how these themes offer future empirical and theoretical research directions for accounting and accountability research in the realm of NGO/non-profit organizations and in organizations more generally.